Brewing The Experiences: Mapping Service Quality And Consumer Behavior In Coffeeshops Through SERVQUAL And Importance Performance Analysis - Achmad Ridha; William Suryanto Limoa (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
This study aims to analyze service quality and consumer behavior among Generation Z customers visiting coffeeshops in Makassar using the SERVQUAL and Importance–Performance Analysis (IPA) models. The research adopts a quantitative descriptive approach with a sample of 100 Gen Z respondents who frequently visit popular and social media–visible coffeeshops. Data were collected using a structured questionnaire adapted from the SERVQUAL framework developed by Parasuraman et al. (1988), comprising 22 indicators distributed across five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The validity and reliability tests confirmed all indicators were valid (r > 0.197) and reliable (Cronbach’s Alpha = 0.903 for perception, 0.866 for expectation). The SERVQUAL analysis revealed negative gap values in all dimensions, indicating that service performance has not fully met customer expectations. The largest gap appeared in responsiveness (–0.49), showing that service promptness and attentiveness require improvement, while tangibles (–0.13) and assurance (–0.05) were relatively better. The IPA results mapped responsiveness indicators into the “Concentrate Here” quadrant, highlighting the need for managerial action, while tangibles and empathy were placed in “Keep Up the Good Work.” Overall, the findings emphasize that Gen Z consumers value fast, interactive, and personalized service experiences, underscoring the urgency for coffeeshop managers to enhance operational agility and technological adaptation to strengthen satisfaction and loyalty.